2008
DOI: 10.3324/haematol.12399
|View full text |Cite
|
Sign up to set email alerts
|

Serum hepcidin level and erythropoietic activity after hematopoietic stem cell transplantation

Abstract: The relationship between serum hepcidin, a key regulator of body iron homeostasis, and erythropoiesis was investigated before and after stem cell transplantation in 31 patients with hematopoietic malignancies. Serum hepcidin-25 was monitored using a liquid chromatography-tandem mass spectrometry-based assay system. Other iron-and erythropoiesis-related parameters and known hepcidin regulators, such as interleukin-6 and growth differentiation factor-15, were also monitored. The serum hepcidin level peaked one w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 23 publications
(26 reference statements)
1
47
0
2
Order By: Relevance
“…[4][5][6] We also identified a hepcidin peak one week after transplantation. Whereas Kanda attributed this peak to inflammation because of a concomitant elevation of serum IL-6 levels (not measured in our study), 5 and although CRP in our study also peaked at Day 7 (data not shown), we did not observe any correlation between hepcidin and CRP values.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 90%
See 2 more Smart Citations
“…[4][5][6] We also identified a hepcidin peak one week after transplantation. Whereas Kanda attributed this peak to inflammation because of a concomitant elevation of serum IL-6 levels (not measured in our study), 5 and although CRP in our study also peaked at Day 7 (data not shown), we did not observe any correlation between hepcidin and CRP values.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 90%
“…Hepcidin is the key regulator of iron metabolism but has been little investigated in the context of HCT. [4][5][6][7] Hepcidin peaked at Day 7 post transplant and then gradually decreased in the following three weeks without returning to pre-transplant levels. 5 In another study, 6 hepcidin levels at 3-5 months post transplant remained unchanged compared to (high) pre-transplant values.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
See 1 more Smart Citation
“…J. Kanda et al performed an in vivo physiological study of the relationship between serum hepcidin and erythropoiesis in the clinical setting of stem cell transplantation (SCT). 22 They monitored the pre-and post-SCT serum hepcidin levels together with other factors potentially affecting hepcidin expression. Four weeks after SCT, at a time when hepcidin levels are no longer related to the inflammatory cytokine IL-6, they found that serum hepcidin levels show a significant inverse correlation with markers of erythropoietic activity, such as the soluble transferrin receptor and the reticulocyte counts, but not with GDF15 levels.…”
Section: Molecular Mechanisms Of Hepcidin Inhibitionmentioning
confidence: 99%
“…Melis et al report a Sardinian inbred family with 5 members affected with IRIDA due to a novel TMPRSS6 mutation, 20 Pagani et al studied the processing of HJV mutants and their ability to activate hepcidin in vitro, 21 while Kanda et al investigated the relationship of hepcidin with markers of erythropoiesis in the stem cell transplantation (SCT) setting. 22 This review summarizes current knowledge of the hepcidin pathway and of the regulation of the hepcidin expression.…”
mentioning
confidence: 99%